Harder, Better, Faster, Stronger? Residents Seeing More Patients Per Hour See Lower Complexity - Corlin M. Jewell; Guangyu (Anthony) Bai; Dann J. Hekman; Adam M. Nicholson; Michael R. Lasarev; Roxana Alexandridis; Benjamin H. Schnapp (Western Journal of Emergency Medicine)
Introduction: Patients seen per hour (PPH) is a popular metric for emergency medicine (EM) resident efficiency, although it is likely insufficient for encapsulating overall efficiency. In this study we explored the relationship between higher patient complexity, acuity on shift, and markers of clinical efficiency. Methods: We performed a retrospective analysis using electronic health record data of the patients seen by EM residents during their final year of training who graduated between 2017–2020 at a single, urban, academic hospital. We compared the number of PPH seen during the third (final) year to patient acuity (Emergency Severity Index), complexity (Current Procedural Terminology codes [CPT]), propensity for admissions, and generated relative value units (RVU). Results: A total of 46 residents were included in the analysis, representing 178,037 total cases. The number of PPH increased from first to second year of residency and fell slightly during the third year of residency. Overall, for each 50% increase in the odds of treating a patient requiring high-level evaluation and management (CPT code 99215), there was a 7.4% decrease in mean PPH. Each 50% increase in odds of treating a case requiring hospital admission was associated with a 6.7% reduction (95% confidence interval [CI] 0.73–12%; P = 0.03) in mean PPH. Each 0.1-point increase in PPH was associated with a 262 (95% CI 157–367; P < 0.001) unit increase in average RVUs generated. Conclusion: Seeing a greater number of patients per hour was associated with a lower volume of complex patients and patients requiring admission among EM residents.